Knock-Out of Tenascin-C Ameliorates Ischemia-Induced Rod-Photoreceptor Degeneration and Retinal Dysfunction - Wiemann, Susanne; Yousf, Aisha; Joachim, Stephanie C.; Peters, Carolin; Mueller-Buehl, Ana M.; Wagner, Natalie; Reinhard, Jacqueline (Frontiers in Neuroscience, 2021)
Retinal ischemia is a common pathomechanism in various eye diseases. Recently, evidence accumulated suggesting that the extracellular matrix (ECM) glycoprotein tenascin-C (Tnc) plays a key role in ischemic degeneration. However, the possible functional role of Tnc in retinal ischemia is not yet known. The aim of our study was to explore retinal function and rod-bipolar/photoreceptor cell degeneration in wild type (WT) and Tnc knock-out (KO) mice after ischemia/reperfusion (I/R) injury. Therefore, I/R was induced by increasing intraocular pressure in the right eye of wild type (WT I/R) and Tnc KO (KO I/R) mice. The left eye served as untreated control (WT CO and KO CO). Scotopic electroretinogram (ERG) recordings were performed to examine rod-bipolar and rod-photoreceptor cell function. Changes of Tnc, rod-bipolar cells, photoreceptors, retinal structure and apoptotic and synaptic alterations were analyzed by immunohistochemistry, Hematoxylin and Eosin staining, Western blot, and quantitative real time PCR. We found increased Tnc protein levels 3 days after ischemia, while Tnc immunoreactivity decreased after 7 days. Tnc mRNA expression was comparable in the ischemic retina. ERG measurements after 7 days showed lower a-/b-wave amplitudes in both ischemic groups. Nevertheless, the amplitudes in the KO I/R group were higher than in the WT I/R group. We observed retinal thinning in WT I/R mice after 3 and 7 days. Although compared to the KO CO group, retinal thinning was not observed in the KO I/R group until 7 days. The number of PKCα+ rod-bipolar cells, recoverin+ photoreceptor staining and Prkca and Rcvrn expression were comparable in all groups. However, reduced rhodopsin protein as well as Rho and Gnat1 mRNA expression levels of rod-photoreceptors were found in the WT I/R, but not in the KO I/R retina. Additionally, a lower number of activated caspase 3+ cells was observed in the KO I/R group. Finally, both ischemic groups displayed enhanced vesicular glutamate transporter 1 (vGlut1) levels. Collectively, KO mice showed diminished rod-photoreceptor degeneration and retinal dysfunction after I/R. Elevated vGlut1 levels after ischemia could be related to an impaired glutamatergic photoreceptor-bipolar cell signaling and excitotoxicity. Our study provides novel evidence that Tnc reinforces ischemic retinal degeneration, possibly by synaptic remodeling.